Degree of Organizational Health availability From the point of view of the workers in the municipality of Albeireh - Masharqa, Odetallah; Eshtaiwy, Mohammad (The Arab Journal of Administration, 2019)
The study aimed at identifying the degree of regulatory health availability from the point of view of the employees of Al-Bireh Municipality and tried to answer the main question (what is the degree of organizational health from the point of view of employees in Palestinian municipalities?). A sample of 78 employees randomly selected from employees of Al-Bireh Municipality, where the total employees in Al- is 102. The study reached a number of results, the most prominent of which were: The degree of approval of the degree of availability of regulatory health in the Palestinian municipalities was average, reaching 65.8%. The indicators of the availability of regulatory health in the Palestinian municipalities in different dimensions are; the average level of integrity and transparency in the Palestinian municipalities was 67.9%, the level of primary and basic structure in the Palestinian municipalities was 67.44%, which is also an average percentage. The results showed that there was no statistically significant difference in the level of (α ≤ 0.05) between the average response of the study sample members to the availability of organizational health in the Palestinian municipalities due to the variables (Age, academic qualification, and years of service). In the light of the results obtained, the study recommended the need to establish mechanisms of administrative accountability in a uniform and fair manner, and that officials in the municipality seek to identify the needs and requirements of the workers, to involve them in the formulation of decisions and to raise constantly their spirits in many ways.